The Role of The Social Counselor in Enhancing The Skill of Assuming Responsibility Among Sixth Grade StudentsA Field Study in Lattakia City (Damascus University Journal of arts and humanities sciences, 2025)
The research aimed to identify the role of the social counselor in enhancing the skill of assuming responsibility among sixth-grade students in schools of Lattakia City. To achieve this, the descriptive approach was used by applying a questionnaire to the research sample consisting of (238) students. The results of the research showed that the role of the social counselor in enhancing the skill of assuming responsibility among students in schools in the city of Lattakia came at a middle degree at the level of the total score of the questionnaire, and the two skills (bearing self-responsibility and assuming collective responsibility) came at a high degree, while the two skills (bearing national responsibility and assuming responsibility moral) to a middle degree. The results also showed that there was a statistically significant difference between the average scores of the answers of members of the research sample on the questionnaire on the role of the social counselor in enhancing the skill of assuming responsibility as a whole among students, and on the two skills (bearing self-responsibility and bearing moral responsibility) according to the gender variable in favor of females.
Keywords: Social Counselor, Skill Of Assuming Responsibility; Basic Education Stage.